INFLUENCE OF BIOFERTILIZER DIFFERENT ON SOME PARAMETERS OF CHEMISTRY IN GROUND PEAT POND - Eka Oktavia Br. Limbong; Syafriadiman '; Saberina Hasibuan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted from October to December 2016 in the PeatLand Kualu Nenas village, Tambang Subdistrict, Kampar Regency, RiauProvince. The aim of this research was to find out the influence of biofertilizerdifferent on some parameters of chemistry in the ground peat pond and todetermine opportune biofertilizer different to increase the productivity of landpeat pond. The method used in this study is an experimental method, using aComplete Random Design (CRD) with 1 factor, 4 treatments, and 3 replications.The treatment used in this experiment is chicken fecal biofertilizer gift (P1), cowfecal biofertilizer (P2), dan human fecal biofertilizer (P3). Result of this researchshow best treatment is human fecal biofertilizer (P3) for pH soil, N total, P total,K total, KBOT, C/N rasio, and soil ammonia, chiken fecal biofertilizer (P1) for Ntotal, C/N rasio, and soil ammonia, cow fecal biofertilizer (P2) for N total, P total,and K total. Water quality of pH range from 5-6,7, DO 4,28-4,75, the best CO2 ishuman fecal biofertilizer (P3) 17,33 mg/l, nitrate 2,45-3,77 mg/l, andorthoposphate 1,64-2,56 mg/l.Keyword : Ground Peat, Chemistry Parameter, and Biofertilizer